Research Funding and Passport Hierarchies: Power Asymmetries in Multi-Sited Ethnographies in Migration Studies - Hannah Pool (Nordic Journal of Migration Research)
This article investigates the asymmetrical power relations between researchers and the researched in the context of multi-sited ethnographies on undocumented migration. Drawing on ethnographic research conducted along migration trajectories linking Afghanistan to Germany in Iran, Turkey, Greece and the so-called Balkan route between 2018 and 2022, the article critically engages with two issues that contribute to the enactment of asymmetrical power relations between migrants and researchers: First, it demonstrates how passport hierarchies determine researchers’ very capacity to conduct multi-sited research and to follow their research interlocutors across borders, privileging those with passports that allow visa-free entry to multiple countries. Second, it highlights how the unequal distribution of research funding determines who can afford to conduct multi-sited research, and how this affects the financial value attached to the time spent by researchers and research interlocutors. Subsequently, it shows how undocumented migrants can – even under highly deprived and precarious conditions – renegotiate these asymmetrical power relations through practices of hosting researchers on their own terms. In this way, the article contributes to a more nuanced understanding of the ethical, power-related and financial challenges present in conducting transnational, multi-sited ethnographies in migration studies.